The Role Community Consumption, Inflation and Human Development Index On Economic Growth In West Java - Suprapto, Hugo Aries; Sumaryoto; Saleh, Sugiyanto (Future Science / FSH-PH Publications, 2022)
The problem of the Covid-19 pandemic that occurred in all parts of Indonesia including the economic growth and the determinants of economic growth were very diverse, including public consumption, inflation and the development of the human index. Stable economic growth had an important impact on people's welfare. There were various factors that can influence economic growth, including public consumption, inflation and the human growth index (IPM). This study aimed to determine the effect of public consumption on community growth, determine the effect of inflation on economic growth, the effect of the human growth index (HDI) on economic growth, and the effect of community consumption, inflation, human growth index (HDI) on economic growth in West Java. The method used was a quantitative method. The data were processed using SPSS 21. The data were taken from the Central Statistics Agency of West Java. The data is in the form of time series from 2015 to 2020. The results of the study explain that there is an influence of community consumption on community growth, there was an effect of inflation on economic growth, and there was an influence of the human growth index (HDI) on economic growth, and the influence of community consumption, inflation, HDI on economic growth in West Java Indonesia. The government should decreased the inflation.